size of the Scottish population of Capercaillie Tetrao urogallus: results of the fourth national survey - Ewing, Steven R; Eaton, Mark A; Poole, Timothy F; Davies, Megan; Haysom, Susan (Bird study, 2012)
Capsule The estimated population size of Capercaillie in Scotland was 1285 individuals (95% CI: 822–1882).Aim To produce an updated population estimate for Capercaillie in Scotland using a similar approach to previous surveys, but with refinements in the sampling design.Methods Line transects were conducted across the Capercaillie's current distribution, sampling in two separate strata: a primary stratum around active lek-sites and a secondary stratum of woodland with recent records of Capercaillie. Multi-covariate distance sampling techniques were used to fit alternative detection functions to Capercaillie sighting data, deriving national and regional abundance estimates.Results Across 629 transects, 61 Capercaillie were observed in 56 encounters, resulting in a population estimate of 1285 individuals (95% CI: 822–1882). This estimate was 35% lower than that derived by the previous survey in 2003–04 but the difference was not statistically significant. The regions of Badenoch and Strathspey were estimated to hold the majority (75%) of the population. The detectability of Capercaillie varied according to habitat type, sex and temperature.Conclusion Imprecision in the national estimates continues to hamper the ability to track changes in the UK population of Capercaillie. However, it is probable that despite recent conservation efforts there has not been a net population increase. Low productivity in recent wet summers, notably in 2007 and 2008, may have countered any beneficial impacts of conservation management.